Meaningful Thresholds for the Volume-Outcome Relationship in Total Knee Arthroplasty. (19th October 2016) - Wilson, Sean; Marx, Robert G.; Pan, Ting-Jung; Lyman, Stephen
Abstract : Background: Increasing evidence supports the finding that patients undergoing a total knee arthroplasty with high-volume physicians and hospitals achieve better outcomes. Unfortunately, the existing definitions for high-volume surgeons and hospitals are highly variable and entirely arbitrary. The aim of this study was to identify a set of meaningful hospital and surgeon total knee arthroplasty volume thresholds. Methods: Using 289, 976 patients undergoing primary total knee arthroplasty from an administrative database, we applied stratum-specific likelihood ratio (SSLR) analysis of a receiver operating characteristic (ROC) curve to generate sets of volume thresholds most predictive of adverse outcomes. The outcomes considered for surgeon volume included 90-day complication and 2-year revision. For hospital volume, we considered 90-day complications and 90-day mortality. Results: SSLR analysis of the ROC curves for 90-day complication and 2-year revision rates by surgeon volume identified four volume categories: 0 to 12, 13 to 59, 60 to 145, and ≥146 total knee arthroplasties per year. Complication rates decreased significantly (p < 0.05) in progressively higher-volume categories. Revision rates followed a similar pattern, but did not decrease between surgeons performing 60 to 145 arthroplasties per year and those performing ≥146 arthroplasties per year. SSLR analysis of 90-day complication and 90-day mortality rates by hospital volume also identified four volume categories: 0 to 89, 90 to 235, 236 to 644, and ≥645 total knee arthroplasties per year. Complication rates decreased significantly (p < 0.05) in progressively higher-volume categories, but the rates did not decrease between hospitals performing 236 to 644 arthroplasties per year and those performing ≥645 arthroplasties per year. Mortality rates for hospitals with ≥645 total knee arthroplasties per year were significantly lower (p < 0.05) than those below the threshold. Conclusions: Our study supports the use of SSLR analysis of ROC curves for risk-based volume stratification in total knee arthroplasty volume-outcomes research. SSLR analysis established meaningful volume definitions for low, medium, high, and very high-volume total knee arthroplasty surgeons and hospitals. This should help patients, surgeons, hospitals, and policymakers to make decisions with regard to the optimal delivery of total knee arthroplasty. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.